Design Principles of the Anode–Electrolyte Interface for All Solid‐State Lithium Metal Batteries. Issue 1 (17th October 2019) - Shen, Zeyu; Zhang, Weidong; Zhu, Guannan; Huang, Yiqiang; Feng, Qi; Lu, Yingying
Abstract: All solid‐state lithium metal batteries (ASSLMBs) provide a promising solution for next‐generation rechargeable energy storage due to their high energy density and the high safety of solid‐state electrolytes (SSEs). However, most SSEs lack thermodynamic intrinsic stability against Li metal and chemical reactions happen spontaneously at the interface when solid‐state electrolytes are in contact with Li metal. An imperfect anode–electrolyte interface is a major hidden danger which restricts electrochemical performances and practical applications of full cells. This review comprehensively analyzes main challenges for anode–electrolyte interfaces in ASSLMBs including poor chemical or electrochemical compatibility, poor ion transport at the interface, and mechanical instability. Exiting strategies focusing on interface engineering are summarized and merits and nonmerits of each method are discussed objectively. The principles and outlooks of interface design are proposed. Meanwhile, advanced characterization and mass production technology are also brought forward to drive the in‐depth study and development of ASSLMBs. Abstract : In this review, the main challenges for the anode–electrolyte interface in all solid‐state lithium metal batteries (ASSLMBs) are analyzed in detail and the corresponding strategies are summarized. Extra attention is paid to the advantages and disadvantages of each method and design principles of anode–electrolyte interface for ASSLMB are proposed from a relatively comprehensive perspective.